The Interplay Between Non-coding RNAs and Insulin-Like Growth Factor Signaling in the Pathogenesis of Neoplasia - Ghafouri-Fard, Soudeh; Abak, Atefe; Mohaqiq, Mahdi; Shoorei, Hamed; Taheri, Mohammad (Frontiers in Cell and Developmental Biology, 2021)
The insulin-like growth factors (IGFs) are polypeptides with similar sequences with insulin. These factors regulate cell growth, development, maturation, and aging via different processes including the interplay with MAPK, Akt, and PI3K. IGF signaling participates in the pathogenesis of neoplasia, insulin resistance, diabetes mellitus, polycystic ovarian syndrome, cerebral ischemic injury, fatty liver disease, and several other conditions. Recent investigations have demonstrated the interplay between non-coding RNAs and IGF signaling. This interplay has fundamental roles in the development of the mentioned disorders. We designed the current study to search the available data about the role of IGF-associated non-coding RNAs in the evolution of neoplasia and other conditions. As novel therapeutic strategies have been designed for modification of IGF signaling, identification of the impact of non-coding RNAs in this pathway is necessary for prediction of response to these modalities.